MENEGUHKAN AKHLAK QUR'ANI DI TENGAH GURITA DIGITAL: RESISTENSI SANTRI ATH THOHIRIYYAH BANYUMAS TERHADAP DEGRADASI MORAL - Arifah Choirun Nisa; Uswatun Hasanah; Lisnawati; M. Misbah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research delves deeply into the cultural resistance strategy developed by the students of the Ath Thohiriyyah Banyumas Islamic Boarding School in maintaining Qur'anic morals in the midst of the onslaught of the digital era. Through a critical ethnographic approach for nine months, this study reveals how students knit moral defense fortresses by activating their cultural, spiritual, and social capital. The findings of the study show that resistance is not carried out confrontationally, but rather through subtle practices such as value encapsulation, cultural hybridization, and identity affirmation. The "Three Layers of Defense" model consisting of internal fortification, community consolidation, and discursive contestation has proven effective in shielding the penetration of destructive digital values. This study concludes that the strength of Qur'anic morality does not lie in isolation from change, but in the ability to conduct creative negotiations with digital modernity. The implication is that pesantren are not only guardians of tradition, but also cultural agents that knit an ethical future in the midst of digital octopus.